The green road - Enright, Anne, 1962- (W.W. Norton & Company, 2015)
"Spanning thirty years, The Green Road tells the story of Rosaleen, matriarch of the Madigans, a family on the cusp of either coming together or falling irreparably apart."--Dust jacket flap.